2019
DOI: 10.47176/mjiri.33.61
|View full text |Cite
|
Sign up to set email alerts
|

Association of socioeconomic risk factors with under 5-year mortality in Zabol, Iran, during 2011-2015

Abstract: Background: Under-5 mortality is an important health indicator of a country's development and every country is committed to decrease it. Children under-5 years are vulnerable to the imbalance of socioeconomic inequality and are dependent on the adults to remain healthy. The aim of this study was to determine the association of socioeconomic factors with under-5 mortality in Zabol. Methods: This descriptive cross sectional study was performed on 2001 children younger than 5 years who were under the coverage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Several previous studies reported social inequalities in under-5 cancer mortality. 15 17 21 This study extended the investigation and found that social inequalities in under-5 cancer mortality risk were greater in the 2010–2014 cohort than in the 1995–1999 cohort.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Several previous studies reported social inequalities in under-5 cancer mortality. 15 17 21 This study extended the investigation and found that social inequalities in under-5 cancer mortality risk were greater in the 2010–2014 cohort than in the 1995–1999 cohort.…”
Section: Discussionsupporting
confidence: 61%
“…The previous studies presented the effects of parents’ socioeconomic conditions 14 15 16 17 18 and the child’s birth conditions (low weight and premature birth) 19 20 on child mortality separately, few studies on the interactive effect of parental social class and low birthweight and preterm birth on under-5 cancer mortality were reported. Therefore, this study attempted to analyze how the social inequalities interact with the child’s birth conditions (low weight and premature birth) and effect on cancer deaths under the age of 5.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital anomalies and prematurity are the leading causes of neonatal death in higher-income countries. Moreover, three major causes of deaths among children aged 1-59 months in the world were pneumonia, other diseases and diarrhea ( Fig 5) (37).…”
Section: Discussionmentioning
confidence: 99%
“…Between 2014-2023, studies from LMICs have examined demographic and socioeconomic factors associated with child mortality. Geographic region/residence [5,[11][12][13][14][15][16][17], ethnicity [18], mother's age [12,17,[19][20][21], marital status [19], sex of child [5], maternal education [5,12,17,19,22], maternal literacy [23], religion [17], breastfeeding [18,21], child death experience [24] place of delivery [5], type of births and delivery [5,11,18,22], high birth order [12], presence of antenatal (ANC) checks [21], tetanus vaccination status [24], contraception use [11][12][13]24], unmet need for family planning [25], distance from health facility [26], mother's working status [20], paternal occupation [13], and household wealth index [5,13,17,…”
Section: Introductionmentioning
confidence: 99%